EFFECT OF BIO-FERTILIZERS AND MOLYBDENUM ON GROWTH AND YIELD OF GREEN BEAN - & Al-Rukabi, Al-Jebory (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at the fields of the Department of Horticulture and Landscape Gardening, College of Agriculture, University of Baghdad, during the spring season of 2015 to study the effect of nitrogen fixing bacterial bio-fertilizers including Rhizobium phaseoli, Azotobacter  chroococcum, and Azospirillum brasilense and molybdenum on growth and yield of green beans. The experiment was conducted according to the randomized complete block design (RCBD) with three replications each included 11 treatments represent the interactions between nitrogen fixing bacteria strains, molybdenum solo application, molybdenum and bacteria strains interactions, in addition to the recommended nitrogen application and control treatment. Results were analyzed using the least significant differences (LSD) test at 5% level of significance. Results showed significant effect of the treatment that included all bacteria strains and Mo (T11) on increasing plant macro elements (N, P, and K) which gave 2.39%, 0.49%, and 2.92%, respectively and Fe and Mo concentrations of 269.67 mg.L-1 and 0.69 mg.L-1, respectively and protein percentage in the pods of 13.98%. in addition, treatment of both R. phaseoli  and A. chroococcum (T5) gave the most significant main root length of 36.56 cm while R. phaseoli  and A. chroococcum and Mo (T9) gave the largest root surface area of 115.00 cm2 and the highest number of root nods that reached 5.33 nod.plant-1. Moreover, T5 significantly increased plant height, leaf number, shoot dry weight, and pod’s length that reached 54.67 cm, 30.22 leaf.plant-1, 65.56 g.plant-1, and 13.62 cm, respectively. As for the T9, results showed significant increase in the number of pods per plant and plant yield of 51.61 pod.plant-1 and 262.03 g.plant-1, respectively.